p53 directly activates cystatin D/CST5 to mediate mesenchymal-epithelial transition: a possible link to tumor suppression by vitamin D3 - Hünten, Sabine (Oncotarget, 2015)
Cystatin D (CST5) encodes an inhibitor of cysteine proteases of the cathepsin family and is directly induced by the vitamin D receptor (VDR). Interestingly, vitamin D3 exerts tumor suppressive effects in a variety of tumor types. In colorectal cancer (CRC) cells CST5 was shown to mediate mesenchymal-epithelial transition (MET). We recently performed an integrated genomic and proteomic screen to identify targets of the p53 tumor suppressor in CRC cells. Thereby, we identified CST5 as a putative p53 target gene. Here, we validated and characterized CST5 as a direct p53 target gene. After activation of a conditional p53 allele, CST5 was upregulated on mRNA and protein levels. Treatment with nutlin-3a or etoposide induced CST5 in a p53-dependent manner. These regulations were direct, since ectopic and endogenous p53 occupied a conserved binding site in the CST5 promoter region. In addition, treatment with calcitriol, the active vitamin D3 metabolite, and simultaneous activation of p53 resulted in enhanced CST5 induction and increased repression of SNAIL, an epithelial-mesenchymal transition (EMT) inducing transcription factor. Furthermore, CST5 inactivation decreased p53-induced mesenchymal-epithelial transition (MET) as evidenced by decreased inhibition of SNAIL and of migration by p53. Furthermore, CST5 expression was directly repressed by SNAIL. In summary, these results imply CST5 as an important mediator of tumor suppression by p53 in colorectal cancer. In addition, they suggest that a combined treatment activating p53 and the vitamin D3 pathway may function via induction of CST5.